Estresse docente, níveis de cortisol e óxido nítrico salivar: um estudo com professores da educação básica - Silva, Regisnei Aparecido de Oliveira (2017)
The present study analyzed the associations between cortisol and salivary nitric oxide (NO) levels as indicators of stress response and its association with the level of perceived stress of male teachers of the State Public Basic Education Network. There are numerous possibilities of studying stress levels, one of these possibilities is through saliva. Studies show that saliva has an immense potential in pointing out disease indicators and, therefore, enabling treatment. Thus, stress situations can be identified by analyzing the salivary components of people under certain conditions, be it work, physical activity or even emotional situations. Among the salivary substances used as biological stress markers we can mention Cortisol and NO that exert influence in several physiological processes of the human organism. The research is characterized as a longitudinal descriptive observational study. Male teachers were selected, totaling 20 participants. The choice of the volunteers was characterized by a non-probabilistic convenience sample, after previous survey of the profile, filling in an identification form, following inclusion and exclusion criteria. The study contemplated the use of the following instruments: Stress Perception Scale and saliva collection. Participants responded to the Cohen and Williamson (1988) validated in Brazil by Reis, Hino and Ricardo-Añes (2010), which he called BPSS-10. The scale was always applied before each day of saliva collection, totalizing 3 scale submissions during the year. The collection of saliva was carried out in a period of one academic year, being made in three specific moments (March, July, December). At each moment three collections of each volunteer were performed on a given day: in the morning, in the fasting; In the lunch interval and at the end of the day, totaled 180 samples. The flasks were kept under refrigeration at -20oC for further saliva analysis. Salimetrics® kit was used to quantify the salivary salivary cortisol by means of an immunoenzymatic assay (EIA), using the kit: High Sensitivity Salivary Cortisol EIA kit (Salimetrics, State College, USA). ), Followed by the protocol determined by the manufacturer. The nitric oxide dosage was performed by indirect measurement of the nitrite formation analyzed by the Griess colorimetric method. The Molecular Probes® Kit (Invitrogen, USA) was used, which contains all reagents required for dosing, including nitrite standards. The data were analyzed by means of descriptive and inferential statistics, considering statistical significance when p <0.05, using the program GrapahPad Prism version 5.00 for Windows and the Microsoft Office Excel program, version 2010. Statistical analysis involved a test of Shapiro-Wilk normality, paired t-test, one-way ANOVA and Bonferroni's post hoc test. The research participants are male teachers with a few years of experience 8.53 ± 7.9 and a mean age of 32 ± 8.22 years. They work with a high workload (46.7 ± 12.6) in at least two schools and half work under a temporary contract. The volunteers surveyed presented a moderate stress level of 16.46 ± 5.36 at the beginning of the school year, 17.53 ± 6.56 at the end of the year, with a marked fall in the holiday period (10.76 ± 5, 64). These data confirm that factors such as the number of schools that work, hours worked, labor situation, among others, can influence the level of teacher stress. The levels of cortisol and salivary NO were presented in crude form and by means of Area Under the Curve (AUC). The mean concentration of salivary cortisol in each period of the day shows that subjects follow a circadian rhythm with high values in the morning, decreasing 5 hours later in all periods of the school year. Regarding the cortisol values obtained through the AUCg the data show that the teachers present a mean cortisol concentration of 1,145μg / dl ± 0,450 at the beginning and 1,031μg / dl ± 0.374 at the end of the school year, decreasing during the vacation period (0.916μg / dl ± 0.341). The data presented do not show a significant relationship (p = 0.7906) between the levels of perceived stress and salivary cortisol during the school year. The results suggest that the teachers, during the vacation period, might not perceive the physiological reactions of stress, so these reactions were not identified by the BPSS-10 used. The NO values presented in AUCg at the three collection moments during the school year did not reveal a significant difference, according to analysis of variance (p = 0.7910). The positive correlation (p = 0.0324) observed between nitric oxide and cortisol levels in the present study reveals that NO may be a biological marker used as a parameter for assessing stress levels. Future studies are needed to confirm the relationship analyzed between NO and salivary cortisol. Therefore, it is important to review methodological aspects, such as the small number of participants.